Turmoil and tranquillity the sea through the eyes of Dutch and Flemish masters, 1550 - 1700 (National Maritime Museum, 2008)
A series of essays and exhibition catalogue, published to accompany the Turmoil and Tranquillity exhibition held at the National Maritime Museum, Greenwich, from 20 June 2008 to 11 January 2009.